Travel Mobile Applications Technology: Examining the Reliability and Validity of Instruments - Nik Alif Amri Nik Hashim, Nurzehan Abu Bakar, Eni Noreni Mohamad Zain, Nur Dalila Mat Yusoff, Nur Hafizah Muhammad (International Journal of Advanced Science and Technology, 2020)
In the existing era of globalization, the Internet acting an important role in people’s lives. It also changes people’s travel style by providing cheaper, easier, and more efficient prices. However, limited attention has been given to the study of young tourists using their mobile phones to book and plan their travels. Therefore, using quantitative methods, the purpose of this pilot study was to evaluate the validity and reliability of the instrument used in measuring the factors that influence the use of travel mobile application technology among tourists in Kuala Lumpur. A sum of 100 data samples were analyzed using the statistical software of IBM SPSS 25. Prior to that, the content and validity of the data, reliability and normality of the data were examined based on expert evaluation. The results of the pilot study indicate that the measurement instruments used in this study are reliable, and the data prove a rational norm. The study’s reults provide overall support for the instruments proposed for further research. Keywords: Mobile Application, Young Traveller, Technology, Kuala Lumpur